A multifunctional lattice sandwich structure with energy harvesting and nonlinear vibration control. (1st August 2019) - Zhang, Ye-Wei; Su, Chang; Ni, Zhi-Yu; Zang, Jian; Chen, Li-Qun
Abstract: A new multifunctional lattice sandwich structure consisting of a lattice sandwich beam, a nonlinear energy sink (NES) and a giant magnetostrictive material (GMM) is proposed in this research. This structure exhibits excellent self-vibration suppression and aeroelastic energy harvesting performance. The dynamic equations of the whole structure are established using Hamilton principle and Newton's second law, and the Runge-Kutta algorithm is used to obtain the amplitude response of the beam coupled with NES and without NES, which can indicate the vibration control effect of NES. Moreover, the energy harvest effect of the structure with GMM is also analyzed through numerical simulation. And a comparative analysis of relevant parameters such as NES mass, spring stiffness and damping coefficient is also implemented. The results show that this new multifunctional lattice sandwich structure can achieve the desired effect of vibration suppression and energy harvesting, and proper adjustment of parameters will improve the effect. This study provides a new idea for related research on vibration control and energy harvesting.